Animal Models of Emerging Tick-Borne Phleboviruses: Determining Target Cells in a Lethal Model of SFTSV Infection - Matsuno, Keita; Orba, Yasuko; Maede-White, Kimberly; Scott, Dana; Feldmann, Friederike; Liang, Mifang; Ebihara, Hideki (Frontiers in Microbiology, 2017)
The pathogenesis of clinical manifestations caused by newly emerging tick-borne phleboviruses [i.e., Severe fever with thrombocytopenia syndrome virus (SFTSV) and Heartland virus (HRTV)], such as severe thrombocytopenia and lymphocytopenia, are not yet fully understood. In the present study, to establish an animal model mimicking the profile of fatal human cases, we examined the susceptibilities of adult mice from 12 strains, aged mice from two strains, and cynomolgus macaques to SFTSV and/or HRTV infections. However, none of these immunocompetent animals developed lethal diseases after infection with SFTSV or HRTV. Thus, we tested a lethal animal model of SFTSV infection using interferon-α/β receptor knock-out (IFNAR–/–) mice to identify the target cell(s) of virus infection, as well as lesions that are potentially associated with hematological changes. IbaI-positive macrophages and Pax5-positive immature B cells overlapped with SFTSV-positive cells in the spleen and lymph nodes of IFNAR–/– mice, and IbaI-SFTSV-double positive cells were also observed in the liver and kidney, thereby suggesting crucial roles for macrophages in the pathogenesis of SFTSV infection in mice. In the mandibular lymph nodes and spleens of infected mice, we observed extensive necrosis comprising B220-positive B cells, which may be associated with severe lymphocytopenia. The results of this study suggest a resemblance between the IFNAR–/– mouse model and lethal infections in humans, as well as roles for multiple cells during pathogenesis in mice.